On Admissible Orders on the Set of Discrete Fuzzy Numbers for Application in Decision Making Problems - Juan Vicente Riera; Sebastia Massanet; Humberto Bustince; Javier Fernandez (Mathematics, 2021)
The study of orders is a constantly evolving topic, not only for its interest from a theoretical point of view, but also for its possible applications. Recently, one of the hot lines of research has been the construction of admissible orders in different frameworks. Following this direction, this paper presents a new representation theorem in the field of discrete fuzzy numbers that enables the construction of two families of admissible orders in the set of discrete fuzzy numbers whose support is a closed interval of a finite chain, leading to the first admissible orders introduced in this framework.